Bio Cad Modeling of Customized Exoskeleton for Rehabilitation of Myopathies and its Fabrication Using Additive Manufacturing - Arumaikkannu, G. (2016)
Additive Manufacturing (AM) is a process of joining materials to make objects from 3D model data, usually layer upon layer, as opposed to subtractive manufacturing methodologies [1]. This paper proposes the benefits of additive manufacturing (AM) within prosthetic device manufacturing, especially for the customization of exoskeleton for Muscular Disorder patients. This work starts with the patient’s CT scan data of the lower limb in DICOM format. This is exported into MIMICS software to stack 2D scan data into 3D model. Then 3D models are imported in to 3matic software, for modeling a Top and Bottom braces with suitable scaling factor, and creates a connecting structural arrangements in proper dimensions. Wall thickness analysis has been carried out in 3matic software, to find out the standard deviation of top and bottom braces, was found to be 1.65mm.The data from clinical gait analysis were determined as, a 100kg system, the torque required for knee extension during stair climbing was 140 Nm and 50 Nm during walking [2]. Through this promising technique the actual process of prosthesis design in rehabilitation technology is improved by applying reverse engineering and additive manufacturing technologies. The outcome of this work is a personalized prosthesis building procedure that should allow an exoskeleton best fit and avoid the numerous iterations done until a proper fit is obtained with traditional methods.